Patch antenna design based on 1D-EBG structures for high gain applications - Sara Said; Sara El Mattar; Ahmed Faize; Abdenacer Es-Salhi; Baghaz Elhadi; Abdennaceur Baghdad (Universitas Ahmad Dahlan, 2023)
In this paper the band gap of one-dimensional electromagnetic band gap (1D-EBG) structures will be determined analytically using the dispersion diagram method. Next, we propose a 1D-EBG antenna design to improve the directivity at 3.5 GHz for WiMax applications. The primary goal of this endeavor is to validate the method and the directive EBG antenna’s design at the resonant frequency 3.5 GHz with optimal adaptation and to demonstrate the effect of the dielectric substrates on increasing the directivity up to 20 dB. The proposed antenna with 1D-EBG shows 14 dBi enhancement in comparison to the conventional antenna without EBG and a very good adaptation is obtained. The design parameters of the antenna were optimized.